Diuretics increase Blood Creatinine in the Treatment of Hypertension (Medico Legal Update, 2021)
Background: Diuretics have been used in the treatment of hypertension by either alone or combining itwith other antihypertensive drugs. It treated about 50% of hypertensive patients alone and about 80% whentreatment was a combination with other antihypertensive drugs. Oral diuretics are used as an initiatingantihypertensive treatment in stepped care approach the antihypertensive management .One such loop diureticcalled as Furosemide is being regularly used in different stages of acute kidney injury and hypertension.Lowering the blood pressure is ultimately reducing the risk of cardiovascular morbidity and mortality. Thesideeffects of diuretics are dose dependent. The intake of Furosemide will bring an increase in the creatininelevel.It must be noted that if the diuretics are been taken for prolong usage, it might over-stress the functionof kidney which will result in sodium resorption increase and elevation of creatinine levels.Material and Method: Twenty hypertensive patients in the age range of 40 to 76 years old were subjectedto a treatment with furosemide(20mg/day) for a variable period of one to three years. The analysis of bloodsamples was being done against the serum creatinine following the colorimetric method. The results werestatistically processed and analyzed by SPSS using the T-test method.Results: The trial was runon the participants being either hypertensive patients or normal individuals. TheMean (+/-SD) of age was 59.4 +/- 10.3, mean (+/-SD) of duration of treatment with furosemide was 2.1 +/-0.7. Mean (+/-SD) of serum creatinine in the control individual was 0.9 +/- 0.22, and mean serum creatininein hypertensive patients treated with furosemide was 2.37 +/- 0.69. (P value < 0.05.)Conclusion: The diuretic Furosemide can increase thelevel of creatinine.Aim of the work: Determine the effect of diuretics (furosemide) on serum creatinine.